Translation and the Quest for Meaning: Adūnīs and Yūsuf al-Khāl's Translation of T. S. Eliot's The Waste Land - Nsiri, Imed (2018)
This article examines some Arabic translations of T.S. Eliot's The Waste Land with special reference to Adunis (͑Ali Ahmad Sa'id) and Yusuf al-Khal's al-Ard al-kharab (1958). Translation requires a close reading of an original text; however, in the case of Adunis's and al-Khal's (1958) al-Ard al-kharab, I found that the translation is the offspring not of one original text, but of an original and a translation, which are Eliot's The Waste Land (1922) and its earliest French translation by Pierre Leyris (1983/1947). The reason for Adunis and al-Khal's (1958) inclusion of and reliance on the French version may be attributed to the fact that, at the time of the translation, Adunis' English was limited - it was, at most, at the intermediate level. The article shall discuss this multiplicity in the recreation of the text viz-a-viz the decisions that Adunis and al-Khal (1958) made to agree or disagree with Leyris' (1983) choices. I shall also use other translations of The Waste Land, such as those by ͑Awad (1968), Lu'lu'ah (1980), and Saqqal (1996) in order: i) to show the other possibilities that Adunis and al-Khal (1958) had in rendering the text into Arabic and, ii) to underscore the point that the choices that they made shed light not only on their activity as translators, but also on the nature of their artistry as poets. Drawing on translation theories and the poetics of translation, the article will have a twofold focus: to trace Adunis and al-Khal's (1958) understanding of a key poem in the development of modern Arabic poetry and their aesthetic principles as they emerge in their decisions, to use Venuti's (1994) terms, to "domesticate" or "foreignize" their translation (p. 20). I will demonstrate how, despite the mistakes that the two poets made, their translation is sound and holds an important place in the history of Arabic literature inasmuch as, on the poetic level, it communicates the essence of the original poem. I conclude that there is ample room for many more translations.